A model of cavitation for the treatment of a moving liquid metal volume. (2nd September 2016) - Lebon, G. S. Bruno; Pericleous, Koulis; Tzanakis, Iakovos; Eskin, Dmitry
Abstract : A homogeneous cavitation model, derived from the Keller–Miksis equation, is developed and applied to the two-phase problem of bubble growth, break-up and propagation in the melt. Numerical simulations of the ultrasonic field emanating from an immersed sonotrode are performed, and the calculated acoustic pressure is applied to the source term of the bubble transport equation to predict the generation, propagation and collapse of cavitation bubbles in the melt. The use of baffles to modify the flow pattern and amplify sound waves in a launder conduit is examined to determine the optimum configuration that maximizes the residence time of the liquid in high cavitation activity regions. The simulation results demonstrate that dimensions that match integer wavelengths, and are therefore in resonance with the travelling waves, are desirable since they lead to an increase in the concentration of nucleating bubbles in the liquid compared with other dimensions.